Pengembangan Model Perencanaan Himpunan Data dan Aplikasi Instrumentasi Berbasis Pola Tujuh Belas Plus - Kusuma, Indra (FITK UIN Walisongo, 2014)
This paper describes the development of a set of data and planning models based instrumentation applications seventeen plus patterns in BK teachers SMP / MTs in Bondowoso. The results of this study indicate that counselling activity planning model using the approach pattern seventeen plus becomes very necessary. B.K. teachers in SMP/MTs of Bondowoso still do not have a wide range of data that should be held for the provision of counselling services. The teachers feel it is important to have variety of data sets and instrumentation applications for the smooth running of counselling services (score = 3.23). The evaluation of the implementation of set of data and applications instrument was still very low (score = 1.14). The planning model development activities and application instrumentation data set found that B.K. teachers desperately need (score = 4.28). The assessment model development planning activities data set and instrumentation applications that are promoted rated excellent (score = 4.47).Â Abstrak Makalah ini menjelaskan pengembangan model perencanaan himpunan data dan aplikasi instrumentasi berbasis pola tujuh belas plus pada guru B.K. SMP/MTs di Bondowoso. Hasil penelitian ini menunjukkan bahwa model perencanaan kegiatan konseling dengan menggunakan pendekatan pola tujuh belas plus menjadi sangat perlu dilakukan agar implementasinya sesuai dengan kebutuhan siswa. Guru BK SMP/MTs di Bondowoso masih banyak yang belum memiliki berbagai data untuk penyelenggaraan layanan konseling. Guru-guru tersebut sangat memerlukan himpunan data dan aplikasi instrumentasi untuk kelancaran menjalankan tugasnya (rerata = 3,23). Sementara evaluasi pelaksanaan himpunan data dan aplikasi instrumennya ternyata masih sangat rendah (rerata = 1,14. Guru-guru BK juga sangat membutuhkan (rerata = 4,28). Penilaian pengembangan model perencanaan kegiatan himpunan data dan aplikasi instrumentasi yang dipromosikan dinilai sangat baik (rata = 4,47)Â